Desain Pelayanan Pastoral Orang Muda Katolik Gereja Santo Yosafat Surabaya menurut Christus Vivit - Kurniawan, Hilarius Andika; Suwito, Benny (Felicitas, 2024)
Young Catholics are called to continue proclaiming faith in the world as modern-day images of Jesus. In Christus Vivit, Pope Francis identifies young people as the "now of the Church" and recognizes their potential to improve the world. As a result, the Church must prepare the formation of young Catholics earnestly. This research explores and designs pastoral care for young Catholics at St. Josafat Church in Surabaya, in line with Christus Vivit. Using qualitative methods, the researcher conducted interviews, surveys, and literature studies to analyze the current pastoral care and develop a new design. While the pastoral movement at St. Josafat Church is active and based on Christus Vivit, it remains focused on bonding and lacks full integration. The general guidelines for the pastoral care of young people at St. Josafat Church Surabaya is aimed to enhance the formation process of young people. These guidelines address several needs specific to the youth, including: building bonding, faith formation, self-recognition and self-potential, leadership development, and the implementation of a missionary spirit. In the next phase, this general guideline for pastoral care for young people according to Christus Vivit will be periodically evaluated to ensure that pastoral care for young people is increasingly optimal and relevant.